Arc instabilities during split anode calorimetry with the TIG welding process - Egerland, Stephan; Colegrove, Paul A.; Williams, Stewart W. (Springer, 2018)
Split anode calorimetry investigations of tungsten inert gas (TIG) arcs were conducted using a large-diameter shielding gas nozzle. Some conditions displayed arc symmetry whilst others proved distinctly asymmetric. The variation of welding current and electrode tip to workpiece distance (ETWD) was studied. Decreasing the ETWD was found to increase the current density towards the arc axis but similar to a previous study of the authors, Gaussian distributions were not observed. The gas nozzle was designed to produce laminar gas flow and sound shielding behaviour; however, anode surface oxidation was found after welding, presumably caused by shielding gas contaminated with oxygen through the welding sequence. Therefore, axial arc symmetry was influenced by random effects. The conditions and reasons for the observed phenomena are explored within this paper.
Keywords: Copper oxide layer; Shielding gas nozzle; Energy density; TIG welding; Split anode calorimetry